Pentagram Geometry - Dibra, Sebhia Marie; Winter, Ulrich (JOURNAL OF ADVANCES IN PHYSICS, 2017)
The Natural Constant Phi is included in the geometrical figure of a Pentagram as many artists have found out. Michelangelo may be the most famous one, whose sketch was transported in the payload of the first sucessful mission to the moon. By deriving this natural constant from the geometrics of the Pentagram a new analytical expression is found for Phi.